ASPEK KEKERASAN SEBAGAI REFLEKSI DAN FORMATIF KONDISI SOSIAL POLITIK DI EKS-TIMOR TIMUR DALAM JAZZ PARFUM & INSIDEN KARYA SENO GUMIRA AJIDARMA - Nurhadi Nurhadi (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2008)
This study aims to describe (1) aspects of violence in short stories in Jazz, Parfum,dan Insiden, (2) socio-political conditions as backgrounds to the violence, (3)the possibility for the fiction to reform society. The data source was Jazz, Parfum, danInsiden by Seno Gumira Ajidarma. The data were analyzed by the content analysisemploying the descriptive qualitative technique. The data trustworthiness was assessedthrough the semantic validity. The findings show that (1) aspects of violenceinclude murder, torture, kidnap, rape, and other types of violence, (2) socio-politicalconditions as backgrounds to the violence are human right violations including theDili incident at the Santa Cruz cemetery on 12 November 1991 and the conditions ofthe occupied East Timor in general, and (3) the fiction has a role in forming readers’awareness of violent acts by government apparatus in the occupation of East Timorby the New Order government that tended to be militaristic and authoritarian. Thefiction indirectly gave contribution to the downfall of the New Order governmentand the independence of Timor Leste.Keywords: violence, East Timor, literature’s reflective role, literature’s formativerole